Cyborg Mind What Brain-Computer and Mind-Cyberspace Interfaces Mean for Cyberneuroethics - MacKellar, Calum (Berghahn Books, 2017)
Should people hardwire computers into their brains, enabling their minds to directly access cyberspace? What advantages and risks would this represent? Would this create a new humanity? These questions have been considered and discussed in science fiction for decades, but technology is beginning to make such developments seem remarkably plausible. This book examines what is currently taking place in this fast-developing sector of society while looking at future prospects. In so doing it seeks to integrate technological and scientific developments, political debate as well as philosophical interrogation while involving ethicists, policy makers, journalists, and practitioners. It is the first extensive study on a topic that is certain to significantly impact the 21st century and beyond. It opens the first door to this important debate.